2008
DOI: 10.1074/mcp.m800037-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Analysis of the Cytoplasmic Proteome of Human Erythrocytes Using the Peptide Ligand Library Technology and Advanced Mass Spectrometry

Abstract: The erythrocyte cytoplasmic proteome is composed of 98% hemoglobin; the remaining 2% is largely unexplored. Here we used a combinatorial library of hexameric peptides as a capturing agent to lower the signal of hemoglobin and amplify the signal of low to very low abundance proteins in the cytoplasm of human red blood cells (RBCs). Two types of hexapeptide library beads have been adopted: amino-terminal hexapeptide beads and beads in which the peptides have been further derivatized by carboxylation. The amplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
219
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 217 publications
(228 citation statements)
references
References 40 publications
8
219
1
Order By: Relevance
“…Furthermore, CPLL have been used for the analysis of human urine, human bile, platelet lysate, red blood cell lysate, chicken egg white and egg yolk, or cow whey (Castagna et al, 2005;Thulasiraman et al, 2005;Guerrier et al, 2006Guerrier et al, , 2007aGuerrier et al, , 2007bD'Ambrosio et al, 2008;Roux-Dalvai et al, 2008;Boschetti and Righetti, 2009;D'Amato et al, 2009;Farinazzo et al, 2009). In all these studies, a much larger number of proteins could be identified when using CPLL, with many of the proteins being described for the first time in the respective sample.…”
mentioning
confidence: 90%
“…Furthermore, CPLL have been used for the analysis of human urine, human bile, platelet lysate, red blood cell lysate, chicken egg white and egg yolk, or cow whey (Castagna et al, 2005;Thulasiraman et al, 2005;Guerrier et al, 2006Guerrier et al, , 2007aGuerrier et al, , 2007bD'Ambrosio et al, 2008;Roux-Dalvai et al, 2008;Boschetti and Righetti, 2009;D'Amato et al, 2009;Farinazzo et al, 2009). In all these studies, a much larger number of proteins could be identified when using CPLL, with many of the proteins being described for the first time in the respective sample.…”
mentioning
confidence: 90%
“…In this context, it appeared that the sequential use of a carboxylated library captured additional species that escaped from the first, aminoterminus, library. This result was obtained from platelet extracts (Guerrier et al, 2007a), from human bile (Guerrier et al, 2007b), as well as from red blood cell lysates (Roux-Dalvai et al, 2008). As an average, the additional proteins caught by the second library represented between 20% and 30% of the total number.…”
Section: The Complementary Effect Of Modified Librariesmentioning
confidence: 85%
“…This goal appears as reachable-at least for simple cells-not only from prokaryotes but also from eucaryotes, such as for instance red blood cells. In a recent presentation, Roux-Dalvai et al (2008) showed that the total count of gene products, that represents the 2% minority RBC cytoplasmic proteome, reached 1,578 unique proteins; U: that is a truly outstanding count, considering that a RBC is a much simplified cell (no nucleus, no other organelles) than any other human cell lines, believed to comprise a genetic asset of >12,000 unique gene products (a mere estimate, because at present, no study has been able to explore to full proteome of any human cell). What is the meaning of such a large body of proteins in the RBC cytoplasm?…”
Section: F Jumping Genes and Stakhanovite Genesmentioning
confidence: 99%
See 2 more Smart Citations